Dyslexic children suffer from less informative visual cues to control posture - Razuk, Milena; Barela, Jose A. [UNESP] (Elsevier B.V., 2014)
The goal of this study was to investigate the effects of manipulation of the characteristics of visual stimulus on postural control in dyslexic children. A total of 18 dyslexic and 18 non-dyslexic children stood upright inside a moving room, as still as possible, and looked at a target at different conditions of distance between the participant and a moving room frontal wall (25-150 cm) and vision (full and central). The first trial was performed without vision (baseline). Then four trials were performed in which the room remained stationary and eight trials with the room moving, lasting 60 s each. Mean sway amplitude, coherence, relative phase, and angular deviation were calculated. The results revealed that dyslexic children swayed with larger magnitude in both stationary and moving conditions. When the room remained stationary, all children showed larger body sway magnitude at 150 cm distance. Dyslexic children showed larger body sway magnitude in central compared to full vision condition. In the moving condition, body sway magnitude was similar between dyslexic and non-dyslexic children but the coupling between visual information and body sway was weaker in dyslexic children. Moreover, in the absence of peripheral visual cues, induced body sway in dyslexic children was temporally delayed regarding visual stimulus. Taken together, these results indicate that poor postural control performance in dyslexic children is related to how sensory information is acquired from the environment and used to produce postural responses. In conditions in which sensory cues are less informative, dyslexic children take longer to process sensory stimuli in order to obtain precise information, which leads to performance deterioration. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Postural control; Dyslexia; Children; Vision; Distance